Manajemen Mutu Sekolah Melalui Kegiatan Paduan Suara Di SDIT Muhammadiyah Al-Kautsar Kartasura Tahun 2016/2017 - Zumratus Sa'adah, Ana; , Dr. Achmad Fathoni, M.Pd (2017)
The research aims to describe: 1) management of choir activities in SDIT Muhammadiyah Al-Kautsar Kartasura, 2) school quality management through choir activities in SDIT Muhammadiyah Al-Kautsar. This type of research is descriptive qualitative research. Data collection techniques used are observation, interviews, and documentation. Data analysis using interactive model. Technique examination of data validity is done by credibility test. The results of the study show that: 1) SDIT Muhammadiyah Al-Kautsar is good in managing choir activities starting from planning including goal setting, execution time, trainer, to inventory of learners who join in activity through questionnaire of registration form; The execution has been compiled by the school of choir activities conducted every Saturday with a variety of songs taught by the coach; Monitoring and evaluation using monitoring books. 2) School quality management through choir activities at SDIT Muhammadiyah Al-Kautsar can be declared good. Quality school management includes quality of input, process quality, and output quality.